Aspek Hukum Hak Menguasai Negara DI Bidang Pertambangan Pasca Pembaruan Undang-Undang Mineral dan Batubara di Indonesia - Andri Yanto; Faidatul Hikmah (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2023)
The concept of State Control Rights, as constitutionally attributed in Article 33 Paragraph (3) of the 1945 Constitution, constitutes a fundamental paradigm. The dialectics of mining policy formulation in Law No. 3 of 2020, which updated the regulation of minerals and coal, ushered in a series of transitions and consequences for the development of the concept of State Control in Indonesia, particularly concerning the substance of Article 4 Paragraph (2) of Law No. 3 of 2020, which introduced the policy of re-centralization. This research employs a juridical-normative method, utilizing a legislative approach and norm analysis pertaining to the concept of State Control Rights. The findings of this study indicate that, firstly, the formulation of state control in Law No. 3 of 2020 aligns intending to implement the concept of State Control as established by the Constitutional Court's decision, emphasizing the permit system as a replacement for the contract system. Secondly, the centralization of authority over mineral and coal mining does not contradict the concept of State Control, as long as it can optimally generate an ideal and effective mining management system in advancing the prosperity of the people. The objective of this research is to provide a comprehensive overview of the application of State Control Rights in the revision of mining legislation, thereby offering policy insights for the development of substantive and just mining law in Indonesia.